Maximizing Chemical Diversity of Fungal Metabolites: Biogenetically Related Heptaketides of the Endolichenic Fungus Corynespora sp.(1) - Wijeratne, E. M. Kithsiri (2010)
In an attempt to explore the biosynthetic potential of the endolichenic fungus, Corynespora sp. BA-10763, its metabolite profiles under several culture conditions were investigated. When cultured in potato dextrose agar, it produced three new heptaketides, 9-O-methylscytalol A (1), 7-desmethylherbarin (2), and 8-hydroxyherbarin (3) together with biogenetically related metabolites, scytalol A (4), 8-O-methylfusarubin (5), scorpinone (6), and 8-O-methylbostrycoidin (7) that are new to this organism, and herbarin (8) a metabolite previously encountered in this fungal strain. The use of malt extract agar as the culture medium led to the isolation of 6, 8, 1-hydroxydehydroherbarin (9), and 1-methoxydehydroherbarin (10), that was found to be an artifact formed during the extraction of the culture medium with methanol. The structures of all new compounds were determined by interpretation of their spectroscopic data and chemical interconversions.